Synthesis of rhodamine chemosensors with high selectivity and sensitivity for multiple metal ions detection / Nur Amira Solehah Pungut - Nur Amira Solehah , Pungut (2021)
Four rhodamine B based chemosensors have been synthesized through condensation reaction between rhodamine B hydrazide with 2-hydroxy-3-methoxybenzaldehyde (RBOV), fluorene-2-carboxaldehyde (RFC), trans-4-(Diethylamino)cinnamaldehyde (RT4) and 3,4,5-trimethoxybenzaldehyde (R3). The compounds were characterized by FTIR, 1H NMR, 13C NMR, mass spectroscopy, and single crystal x-ray diffraction. These chemosensors exhibit different and unique properties as RBOV can detect Cu2+, Ni2+ and Co2+ ions, RFC is able to detect Al3+ and Cu2+ ions, RT4 detects Cu2+ and Fe3+ ions and R3 is able to detect Fe3+ ions only. The detection of these metal ions was further investigated using UV-vis and fluorescence spectroscopy. For all sensors, a 1:1 binding stoichiometry of the chemosensors-metal ions were determined through Job’s plot analysis while the detection limit (in μM) of the chemosensors were determined from the UV-vis and fluorescence titration experiments. Furthermore, the binding of the chemosensors with the metal ions were also illustrated by the partial FTIR and 1H NMR spectrum. In determining the potential application of the sensors both biologically and environmentally, reversibility, test strips and MTT assays have been successfully prepared and studied.